Numerical and experimental investigations on heat transfer and pressure drop characteristics of Al 2 O 3 -TiO 2 hybrid nanofluid in minichannel heat sink with different mixture ratio - Kumar V.; Sarkar J. (My University, 2025)
Heat transfer and pressure drop characteristics of minichannel heat sink are analysed experimentally and numerically (two-phase mixture model) by using hybrid nanofluids. Minichannel heat sink consists of 9 parallel rectangular shaped minichannels having depth of 3 mm and width of 1 mm. The Al 2 O 3 –TiO 2 hybrid nanofluid with nanoparticles volume concentration of 0.1% with different nanoparticle mixture ratios (10:0 to 0:10) has been used as coolant to analyze the effect of volume flow rate (0.1 to 0.5 LPM), Reynolds number (90 < Re < 500) and inlet temperature (20 to 40 °C). Two-phase mixture model has good agreement with the experiment data as compared to single phase (homogenous model) approach. The developing length slightly increases by using hybrid nanofluid. A maximum enhancement of 8.5% (numerical) and 12.8% (experimental) has been observed for convective heat transfer coefficient with Al 2 O 3 (10:0) hybrid nanofluid. Pressure drop and friction factor increase with decrease in temperature and increase in volume fraction of nanoparticles. Both numerical and experimental results reveal that the hybrid nanofluids yield no synergetic effect in heat transfer while mixing dissimilar nanoparticles with similar shape and size. © 2019 Elsevier B.V.